2021
DOI: 10.3389/fonc.2021.620912
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of TARBP2 Drives the Progression of Hepatocellular Carcinoma via miR-145-SERPINE1 Axis

Abstract: The clinical outcomes of hepatocellular carcinoma (HCC) remain dismal. Elucidating the molecular mechanisms for the progression of aggressive HCC holds the promise for developing novel intervention strategies. The transactivation response element RNA-binding protein (TRBP/TARBP2), a key component of microRNA (miRNA) processing and maturation machinery has been shown to play conflicting roles in tumor development and progression. We sought to investigate the expression of TARBP2 in HCC using well-characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…When HCC cells were exposed to various doses of lenvatinib, the expression of AKR1C1 was upregulated, while that of SERPINE1 was downregulated. According to the obtained results, lenvatinib can inhibit the expression of SERPINE1 (an oncogene in HCC) in HCC cells, regardless of the concentration (16,17). This indicated that SERPINE1 was the target of lenvatinib, and in HCC patients with a high expression of SERPINE1, lenvatinib can be used for targeted treatment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…When HCC cells were exposed to various doses of lenvatinib, the expression of AKR1C1 was upregulated, while that of SERPINE1 was downregulated. According to the obtained results, lenvatinib can inhibit the expression of SERPINE1 (an oncogene in HCC) in HCC cells, regardless of the concentration (16,17). This indicated that SERPINE1 was the target of lenvatinib, and in HCC patients with a high expression of SERPINE1, lenvatinib can be used for targeted treatment.…”
Section: Discussionmentioning
confidence: 70%
“…The PPI network of DEGs demonstrated that AKR1C1 was the most prominent upregulated gene in LEN-MHCC-97H cells, and serpin family E member 1 (SERPINE1) was a considerably downregulated gene in LEN-MHCC-97H cells (Figure 3B,3C, Tables 2,3). SERPINE1 promotes the proliferation, invasion, migration, and epithelial-mesenchymal transition (EMT) of HCC cells (16,17). However, the function of AKR1C1 in HCC is not clear.…”
Section: Identification and Validation Of Targets For Lenvatinib In Hccmentioning
confidence: 99%
“…The luciferase reporter assay was performed in 48-well plates as described previously ( 14 ) with the protocol of the manufacturer using the dual luciferase assay kit from Promega (Madison, WI, USA). HUVEC cells were grown and co-transfected with 100 ng of a firefly luciferase reporter plasmid pGL3 carrying different wild-type or mutant constructs or the Renilla luciferase vector pRL-TK (5 ng; for normalization) from Promega using Lipofectamine 2000 transfection reagent (Invitrogen, Carlsbad, USA) according to the protocol of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have reported that HBV contributes to the proliferation and metastasis of liver cells, playing a crucial role in the high recurrence and mortality of liver cancer (3)(4)(5). Despite improvements that have been made in surgical resection and transplantation, the prognosis of patients with liver cancer remains unsatisfactory with a 5-year survival rate of <50% (6,7). Therefore, exploring the molecular mechanism underlying the pathogenesis of HBV-associated liver cancer has important clinical significance.…”
Section: Introductionmentioning
confidence: 99%